1970
DOI: 10.3329/fmcj.v6i1.7404
|View full text |Cite
|
Sign up to set email alerts
|

Role of Urinary Albumin in the Prediction of Preeclampsia

Abstract: To explore a suitable biochemical marker to predict the future development of preeclampsia (PE), total 119 pregnant women at their 10-14 weeks of pregnancy were selected. Urinary albumin was measured in these subjects and they were followed up to the term for the possible development of PE. The data were analyzed by grouping the subjects into the PE group and control group. Out of 119 subjects 56 were primigravida and 63 were multigravida. From the total subjects 10 developed PE (04 primigravida and 06 multigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
7
4
0
Order By: Relevance
“…We found that the spot urinary ACR at 20-28 weeks of gestation was significantly higher in women who subsequently developed pre-eclampsia with mean value of 51.95 ± 18.78 mg/mmol and then in those who remain normotensive with mean value of 19.26 ± 7.99 mg/mmol. Baweja et al [9] and Fatema et al [11] found the similar results in their studies. The sensitivity of ACR at cut-off value of C35.5 mg/mmol as screening test to predict pre-eclampsia in our study was found to be 87.5% which is comparable to the studies done by Baweja et al [9] (83.3%) and Fatema et al [11] (80%).…”
Section: Discussionsupporting
confidence: 73%
“…We found that the spot urinary ACR at 20-28 weeks of gestation was significantly higher in women who subsequently developed pre-eclampsia with mean value of 51.95 ± 18.78 mg/mmol and then in those who remain normotensive with mean value of 19.26 ± 7.99 mg/mmol. Baweja et al [9] and Fatema et al [11] found the similar results in their studies. The sensitivity of ACR at cut-off value of C35.5 mg/mmol as screening test to predict pre-eclampsia in our study was found to be 87.5% which is comparable to the studies done by Baweja et al [9] (83.3%) and Fatema et al [11] (80%).…”
Section: Discussionsupporting
confidence: 73%
“…11,12 The sensitivity of spot UPCR at the cut-off value of ≥ 35.5 mg/mmol as a screening test to predict preeclampsia in our study was found to be 80% which is comparable to the studies done by Baweja et al, (83.3%), Fatema et al, (80%) and Mishra et al, (87.5%). [11][12][13] In the present study abnormal uterine artery doppler indices (RI > .0.7/PI > 1.4/ presence of diastolic notch) were associated with increased risk of developing preeclampsia in later part of pregnancy. The cut-off value of RI and PI was similar with the study of Sahoo et al 14 Razieh DF et al, found that 23 pregnancies (85.2%) with preeclampsia had RI more than 0.7 and only 4 (14.8%) had RI < 0.7 (p = 0.001).…”
Section: Discussionsupporting
confidence: 86%
“…They concluded that the test was sufficient enough to predict the possibility of pre-eclampsia. Although their inference was comparable with the ones presented by Baweja S. et al 15 (83.3% sensitivity) and Fatema K et al 16 (80% sensitivity), but the study consisted of a very small sample size.…”
Section: Discussionsupporting
confidence: 85%